Effects of temperature-dependent properties on wire-coating from a bath of FENE-P fluid. (December 2016) - Ali, Nasir; Javed, Muhammad Asif
Highlights: The wire-coating problem is modeled for constant and variable physical properties. The exact solutions ​ are obtained for constant physical properties. For variable physical properties, the problem is solved numerically. The effects of various involved parameters are analyzed graphically. Abstract: An analysis is carried out to study theoretically the coating of wire by drawing it from a pool of viscoelastic fluid in a pressure type-die under non-isothermal conditions. The constitutive equation of FENE-P model is used to characterize the rheology of the polymer melt. The equations describing the flow and heat transfer inside the die are solved (a) analytically for constant physical properties (b) numerically for temperature-dependent fluid properties. In the former case, the analytical expressions of velocity, volumetric flow rate, final radius of the coated wire and force required to pull the wire are reported. In the latter case, the fluid viscosity and relaxation time are considered as a function of temperature. The well-known Nahme–Griffith law is used to capture such dependence. Shooting method with Runge–Kutta–Fehlberg algorithm is employed to solve the coupled energy and momentum equations. The effects of different parameters on the velocity and the temperature distributions, volumetric flow rate, final thickness of the coated wire and force necessary to pull the wire are illustrated graphically for both the cases of constant and variable physical properties.